PTH-001 A National Survey of Local Hereditary Colorectal Cancer Services in the UK; A Highly Variable Approach?. (4th June 2013) - Monahan, K J; Clark, S K
Abstract : Introduction: The identification of inherited gastrointestinal disease provides an opportunity to prevent colorectal cancer. Heritable factors contribute about 35% of all colorectal cancer risk which has a significant impact on clinical activity in centres managing colorectal cancer. The British Society of Gastroenterology (BSG) and Association of Coloproctologists of Great Britain and Ireland (ACPGBI), released updated guidelines in 2010 for the management of patients with a family history of colorectal cancer. There is evidence that adherence to these guidelines is highly variable both for endoscopic screening and testing individuals for inherited conditions such as Lynch Syndrome and the Polyposis Syndromes. The aim of this survey was therefore to facilitate understanding of how services for patients with inherited colorectal cancer risk can be improved, and to raise awareness of this issue amongst clinicians. Methods: Following consultation within the BSG Cancer Group, UK Gastroenterologists, Colorectal Surgeons, Clinical and Medical Oncologists were invited to complete a short 10 point questionnaire. This was cascaded by email to 1, 793 members of the Royal College of Radiologists (RCR), Association of Cancer Physicians (ACP), the BSG and ACPGBI. We sought their opinion and perception of local hereditary colorectal cancer services, also their adherence to and understanding of current national guidelines. Results: Three hundred and eighty-two members responded to the survey, an overall response rate of 21.3%. Although 69% of respondents felt there was an adequate service for these patients, 64% also believed that another clinician was undertaking this work. There was no apparent patient pathway in 52% of centres, and only 33% maintain a register of these patients. Patients rarely receive initial tumour block testing for Lynch Syndrome. When asked what they would like to augment the service they receive many respondents requested 'clear guidelines', 'pathways' and dedicated support networks. Many appeared to be unaware of the BSG/ACPGBI guidelines for the management of these patients. Conclusion: There was wide variability in practise and in pathways for hereditary colorectal cancer patients with a perception that they should be managed by another unspecified clinician. BSG/ACPGBI National Guidelines are not adhered to, therefore we recommend improved education, well defined pathways and audit in order to improve care of patients with hereditary colorectal cancer risk. Disclosure of Interest: None Declared.